Study of Peroxidase Enzyme and Related Trace Elements in Serum and Saliva of Patients with Oral Epithelial Tumors - R. Hasan, Hathama; M. Dawood, Rukzan (Asian Journal of Chemistry, 2012)
The present study was designed to investigate the changes in the activity and specific activity of peroxidase and related to iron concentration in serum and saliva samples of patients with oral epithelial tumors (benign and malignant). Anodic and cathodic conventional PAGE (7.5 %) were used to illustrate the changes of the enzyme due to the presence of the tumor. Thirty three patients with oral tumor (benign and malignant) aged 15-75 years attending the specialized surgery hospital/Baghdad medical city were include in this study. Thirty two healthy individuals of matched age and gender were utilized as control. The results indicated the presence of highly increase (p < 0.001) of both serum and salivary peroxidase activity (U/L) in both benign and malignant groups in comparison to that of control. The specific activity of peroxidase showed a significant increase (p < 0.05) in saliva sample of benign group. Serum iron concentration results showed a highly significant decrease (p = 0.01), (p < 0.01) in benign and malignant groups respectively in comparison to the control, while the salivary iron concentration showed a highly significant and significant increase (p = 0.001), (p = 0.05) in benign and malignant groups respectively. The ratio of iron concentration/peroxidase activity showed a significant difference (p < 0.01) in serum samples of benign and malignant groups in comparison to the control.